Detecting the pH-dependent liquid-liquid phase separation of single levitated aerosol microdroplets via laser tweezers-Raman spectroscopy - Tong, Yu-Kai; Meng, Xiangxinyue; Zhou, Bo; Sun, Rui; Wu, Zhijun; Hu, Min; Ye, Anpei (Frontiers in Physics, 2022)
Ambient atmospheric aerosol particles comprised of various inorganic and organic substances ubiquitously undergo phase transition, such as efflorescence, amorphization, and especially liquid-liquid phase separation (LLPS). Resultant changes of physicochemical properties in aerosols then deeply affect the climate system. However, finely detecting these processes occurring in single aerosol particles, especially under the acidic condition of real atmospheric environment, remains a challenge. In this work, we investigated the pH-dependent phase separation in single levitated microdroplets using a self-developed laser tweezers Raman spectroscopy (LTRS) system. The dynamic process of LLPS in laser-trapped droplets over the course of humidity cycles was detected with the time-resolved cavity-enhanced Raman spectra. These measurements provide the first comprehensive account of the pH-dependent LLPS in single levitated aerosol microdroplets and bring possible implications on phase separation in actual atmospheric particles.